Arabic Language and Medical Terminology in Education: A Systematic Review - Mohamed Sapawi, Mior Syazril; Nik Yusoff, Nik Mohd Rahimi (IIUM Medical Journal Malaysia, 2026)
The use of Arabic in medical education and healthcare communication remains limited despite growing linguistic needs in Arabic-speaking populations. Issues related to translation accuracy, cultural sensitivity, and curriculum alignment hinder its integration. The objective of this study is to systematically review how Arabic medical terminology has been translated, validated, and applied in educational and clinical contexts. This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. Searches were conducted in May 2025 across three databases: Scopus, Web of Science (WoS), and the Education Resources Information Center (ERIC). A total of 769 records were retrieved, and 19 peer-reviewed articles were selected based on inclusion criteria. A six-point quality appraisal framework was applied to ensure methodological rigour prior to thematic synthesis. Three major themes emerged: (1) translation and cultural adaptation, highlighting the importance of expert validation and semantic accuracy; (2) psychometric evaluation, where tools such as the Postgraduate Hospital Educational Environment Measure (PHEEM) demonstrated strong internal consistency and contextual clarity; and (3) educational application, showing varied success in enhancing communication, comprehension, and learner confidence. Gaps in terminology standardisation and the limitations of automated translation tools were noted across studies. In conclusion Arabic medical terminology, when supported by structured processes and expert review, makes a meaningful contribution to education and communication. Further efforts should prioritise the development of validated terminology repositories, multidisciplinary collaboration, and the integration of Arabic-language resources into medical curricula to support inclusive and patient-centred care.